Pengaruh Citra Merek dan Kualitas Produk terhadap Loyalitas Pelanggan (Studi pada McDonald’s Cabang Ciledug) - Rizka Fajrina; Muhammad Azhar; Mawaddatul Ulya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study is motivated by the boycott phenomenon against McDonald’s triggered by the Israel–Palestine conflict, which has affected consumer perceptions in Indonesia, particularly in Ciledug, Tangerang City. The purpose of this research is to analyze the influence of brand image and product quality on customer loyalty toward McDonald’s in Ciledug District. The research method employed is quantitative utilizing a purposive sampling technique, with 100 respondents who are McDonald’s consumers. Data processing was conducted using SPSS version 23, including multiple linear regression analysis, validity and reliability tests, classical assumption tests, F-test, t-test, and the coefficient of determination (R²). The findings reveal that brand image has a positive and significant effect on customer loyalty, indicated by t-count > t-table, with a value of 9.268 > 1.984. Meanwhile, product quality does not show a significant effect on customer loyalty, reflacted by t-count < t-table, with a value of -0.381 < 1.984. Simultaneously, brand image and product quality highly influence customer loyalty, as presented by F-count 103.713 > F-table 3.090 and a significance value of 0.000, which is less than 0.05.